PHBS (Clean and Healthy Living Habits) As Covid 19 Prevention Education for Early Childhood - Abdullah Abdullah; Handono Fatkhur Rahman; Wiwin Warliah; Nur Qomariah; Sutriyani Sutriyani (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2022)
This research was motivated by the PHBS movement (Habitat for Clean and Healthy Life); PHBS was carried out at an early childhood education program, namely Raudlatul Athfal, located in the village of Pakunira. This study aims to determine how PHBS in children is early prevention of COVID 19. This study used a descriptive qualitative approach. Data collection techniques using interviews, observation, and documentation. After that, it is processed through data triangulation. PHBS is carried out in preparation and planning analysis, PHBS program implementation, and program evaluation based on the research findings. This research has implications for covid-19 prevention education through PHBS to provide the understanding and habituation to healthy lifestyles for students, teachers, parents, and the school environment